Impacts of leachates from single-use polyethylene plastic bags on the early development of clam Meretrix meretrix (Bivalvia: Veneridae). (May 2019) - Ke, Ai-Ying; Chen, Jian; Zhu, Jie; Wang, Yao-Hua; Hu, Yuan; Fan, Zheng-Li; Chen, Man; Peng, Peng; Jiang, Shu-Wen; Xu, Xiang-Rong; Li, Heng-Xiang
Abstract: Plastic debris in the oceans is a major and growing problem in global environmental pollution. There are increasing concerns that plastic debris is a source of contaminant, either added during manufacturing or adsorbed from the environment. However, there is little information about the acute toxicity of leachates from plastic debris on marine organisms. In this study, we conducted experiments to evaluate the toxicity of leachates from two single-use polyethylene plastic bags (PB1 and PB2) with the embryo and larvae of the commercial clam Meretrix meretrix . Results showed that fertilization of the embryos was not affected by plastic leachates, but the developments of D-veliger larvae, including survival, deformity, and shell height, were significantly affected by plastic leachates from both PB1 and PB2 compared to the controls of filtered seawater. We speculate that compounds leaching from plastic bags are responsible for the observed toxicity. Therefore, leaching toxicity from plastic debris should be considered when assessing the risks of plastic pollution in the oceans. Highlights: Acute toxicity of plastic leachates was evaluated on the early development of clams Meretrix meretrix . Fertilization of clam embryos was not affected by the plastic leachates. Developments of D-veliger larvae were impaired by leachates from two plastic bags. Leaching of chemicals from plastic bags might be responsible for the observed toxicity.